2008
DOI: 10.1002/pca.1086
|View full text |Cite
|
Sign up to set email alerts
|

Application of Scion image software to the simultaneous determination of curcuminoids in turmeric (Curcuma longa)

Abstract: TLC image analysis using Scion Image is shown to be a reliable method for the simultaneous analysis of the content of each curcuminoid in turmeric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…32 P labeled-proteins were detected by autoradiography. Densitometric measurements were quantified using Scion image software 48 .…”
Section: Methodsmentioning
confidence: 99%
“…32 P labeled-proteins were detected by autoradiography. Densitometric measurements were quantified using Scion image software 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Chromatographic methods are extensively used for quantitative analysis of curcuminoids and also for fingerprint analysis of Curcuma species. A number of qualitative and quantitative analysis of curcuminoids using thin layer chromatography (Sotanaphun et al 2009), HPLC with UV or fluorescence detector (Jadhav et al 2007;Wichitnithad et al 2009;Cheng et al 2010;Li et al 2011), liquid chromatography-mass spectrometry (LC-MS) (Verma et al 2013), micellar electrokinetic chromatography (Watanabe et al 2000), and capillary electrophoresis (Lechtenberg et al 2004;Anubala et al 2014) have been reported in various Curcuma samples. In the chromatographic fingerprint analysis of Curcuma species, the reported analytical instruments used are HPLC (Li et al 2011;Lee et al 2014) and GC (Lee et al 2014;Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Photoshop 7.0 and Scion image software were chosen to determine the amount of three curcuminoid in Curcuma longa. The techniques were validated and showed to be accurate and reliable method [16][17] .…”
Section: Discussionmentioning
confidence: 99%